Understanding and Managing Conflict.pdf - Diin Fitri, SE., MM. (Management and Leadership Study Programme, 2018)
Conflict is normal phenomena in organizations. It is part of organization life. It shows that organization is healthy when there are conflicts until one point as it shows the process of changing and learning. Thus, it will be beneficial for the organizations to understand the source, type of conflict and be able to manage conflicts. This is a qualitative research based on literature review to find the source, type of conflict and to provide practical guidelines on how to manage conflict. It is found that that several sources of conflict such as communication, cultural diversity and unmet expectation and needs. Previous researchers classified conflicts into different terms such as structure, process and tasks, and conflict into individual, intergroup and process conflict. Some practical guidelines were also provided, but communication is a major point.,